Model Picture Project Investigation Untuk Menilai Aktivitas Dan Hasil Belajar IPA Di SD - Nazira Sa’ida; Darmiyati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The issue is the low action and learning results of understudies. Endeavors were made utilizing the Undertaking Based Learning model, Gathering examination, and Endlessly picture. The motivation behind this study is to depict instructor exercises, to dissect understudy learning exercises and results. The methodology utilized in this exploration is a subjective methodology with the sort of Homeroom Activity Exploration which is done in three gatherings. The examination setting was completed at SD Muhammadiyah 1 Banjarmasin for class IV understudies with a sum of 18 understudies for the 2022/2023 scholarly year. The kinds of information in this study are subjective information and quantitative information. Information investigation is determined in light of the rate scale and learning dominance pointers that not entirely set in stone. The consequences of the review show that at the third gathering it shows that the educator's movement gets a score of 39 withthe criteria of "Very Good". Student activity scores 89.00% with very good criteria. Student learning outcomes get a classical score with a score of 100%. Based on these findings, the implications of this combination of models can increase activity and learning outcomes. The results of this research are expected to be valuable information for school principals to adopt the most appropriate policy in terms of efforts to present effective and efficient learning strategies in schools.